Exploring the potential mechanisms of the Prunus mume-Prunella vulgaris herb pair in treating endometrial polyps based on network pharmacology and molecular docking - Wen Yan Zhang; Yuan Yuan; Li Fan; Guang Rong Huang; Shu Yu Pan; Jing Xiao (Molecular Genetics and Genomics, 2026)

Temporal trends in toxicities and major drivers of polycyclic aromatic hydrocarbon emissions in China from 1960 to 2019 - Xiao Yun; Huizhong Shen; Jin Li; Yuanzheng Zhang; Shuxiu Zheng; Rong Dai; Jinghang Wang; Haoran Xu; Wenxiao Zhang; Guofeng Shen; Jianmin Ma; Shu Tao (Atmospheric Environment, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

AI-decoded enzymatic blueprints navigate the unknown metabolome - Shu-Xin Cao; Xiang Luo; Yu Bai; Hong-Li Tan; Rong-Rong He (Science China Life Sciences, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Protein foundation models: a comprehensive survey - Hao Xu; Liangjie Li; Sangyu Pan; Peng Cheng; Yuxiang Wang; Zhen Rong; Feng Liu; Xingxu Huang; Shengqi Wang; Wenjie Shu (Science China Life Sciences, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Quantification and geological implications of manganese, barium, and copper observed by MarSCoDe LIBS at Zhurong landing site on Mars - Yuxuan Luo; Zhaopeng Chen; Jianjun Liu; Yizhong Zhang; Jingjing Zhang; Zhibin Li; Xin Ren; Xiangfeng Liu; Zhenqiang Zhang; Weiming Xu; Guolin Hu; Shaojin Han; et al. (Icarus, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Anti-interference detection of Pb (II) in seawater enabled by a photo-electrostatic ZnFe2O4/MoS2 heterojunction electrode - Shu Huo; Rong Guo; Gengchen Li; Hong Liu; Wenbo Hang; Tingting Liu; Ye Ma; Minggang Zhao (Chemical Engineering Journal, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

The late Eocene pine seed cones from Mangkang Basin, southeastern Xizang (Tibet) and their biogeographic significance - Xuan-Rong Yao; Yi Gao; Ren-Dan Yang; Jiang-Bo Meng; Shu-Feng Li; Tao Su (Palaeoworld, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Discovery of novel potential 11β-HSD1 inhibitors through combining deep learning, molecular modeling, and bio-evaluation - Xiaodie Chen; Liang Zou; Lu Zhang; Jiali Li; Rong Liu; Yueyue He; Mao Shu; Kuilong Huang (Molecular Diversity, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Effects of stress factors on biogenic isoprene emissions and their contribution to ozone and secondary organic aerosols in China - Rong Song; Tijian Wang; Bingliang Zhuang; Mengmeng Li; Shu Li; Min Xie (Science of The Total Environment, 2025)

Pseudomonas chlororaphis ZH2: Evaluation of the Biocontrol Potential of Continuous Cropping Obstacles on the Basis of Genome Analysis, Autotoxic Substance Degradation and In Vitro Antifungal Activity - Rong Xiao; Chunfen Zhang; Shu Deng; Ciqiong Niu; Quan Li; Junjie Sun; Juantao Liu; Jianping Wang (Current Microbiology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Mechanism of antimony oxidation and adsorption using immobilized Klebsiella aerogenes HC10 in soil - Qun Rong; Dingtian Lu; Kai Zhong; Shu Yang; Zhongyi Li; Chaolan Zhang (Science of The Total Environment, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Photocorrosion suppression of copper sulfide via hybridization with amino-functionalized metal–organic framework for natural sunlight-driven photocatalysis - Zewei Liu; Cheng Tang; Zepeng Yu; Shu Li; Chengzhang Deng; Sijie Liu; Zhiqiang Wu; Rong Tan (Fuel, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Application of luminescent Photobacterium Phosphoreum T3 for the detection of zearalenone and estimating the efficiency of their enzymatic degradation - Shu-Rong Chen; Li-Hong Chen; Li Pan; Bin Wang (Food Additives & Contaminants: Part A, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Characterization of multi-copy C3 genes and association analysis of C3.1 polymorphism with GCRV resistance traits in Ctenopharyngodon idella - Jia-yang Huang; Zhao Lv; Bin Li; Yan-rong Ying; Le Yang; Tiao-yi Xiao; Shu-ting Xiong (Aquaculture, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Metabonomics analysis of microalga Scenedesmus obliquus under ciprofloxacin stress - Yue Wang; Weihao Ning; Shengnan Li; Changfei Gao; Rong Cui; Wanqian Guo; Jo-Shu Chang; Shih-Hsin Ho (Environmental Research, 2023)

Mesoscopic measurement of damage and shear bands of granite residual soil using Micro-CT and digital volume correlation - Cheng-sheng Li; Bing-xin Zhang; Zhi-jun Liu; Ling-wei Kong; Rong-jun Shu (Journal of Mountain Science, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Simultaneous removal of sulfamethoxazole during fermentative production of short-chain fatty acids - Yue Wang; Rongrong Lin; Yushuang Cao; Shuangfei Li; Rong Cui; Wanqian Guo; Shih-Hsin Ho; Yoong Kit Leong; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Catalytic probes based on aggregation-induced emission-active Au nanoclusters for visualizing MicroRNA in living cells and in vivo - Wenhao Shu; Xuetao Zhang; Hongmei Tang; Linna Wang; Manxiao Cheng; Jingwen Xu; Rong Li; Xiang Ran (Analytica Chimica Acta, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Amendments of nitrogen and sulfur mitigate carbon-promoting effect on microbial mercury methylation in paddy soils - Yunyun Li; Shu-Shen Dai; Jiating Zhao; Zhi-Cheng Hu; Qin Liu; Jiao Feng; Qiaoyun Huang; Yuxi Gao; Yu-Rong Liu (Journal of Hazardous Materials, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

The mutual interactions among ozone, fine particulate matter, and carbon dioxide on summer monsoon climate in East Asia - Danyang Ma; Tijian Wang; Beiyao Xu; Rong Song; Libo Gao; Huimin Chen; Xuejuan Ren; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Eri Saikawa (Atmospheric Environment, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Enhanced preservation effects of clove (Syzygium aromaticum) essential oil on the processing of Chinese bacon (preserved meat products) by beta cyclodextrin metal organic frameworks (β-CD-MOFs) - Ying Wang; Yi-Tong Du; Wan-Yu Xue; Liang Wang; Rong Li; Zi-Tao Jiang; Shu-Hua Tang; Jin Tan (Meat Science, 2023)

Impacts of meteorological factors and ozone variation on crop yields in China concerning carbon neutrality objectives in 2060 - Beiyao Xu; Tijian Wang; Libo Gao; Danyang Ma; Rong Song; Jin Zhao; Xiaoguang Yang; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie (Environmental Pollution, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

Comment on “Relationship of Circulating Copper Level with Gestational Diabetes Mellitus: a Meta-analysis and Systemic Review” - Shu-ping Li; Xiao-ping Zhang; Xin-hong Cui; Li-juan Zhao; Yan-jun Rong (Biological Trace Element Research, 2022)

Salicylic acid alleviates selenium stress and promotes selenium uptake of grapevine - Zhiyu Li; Rong Fan; Xuemei Peng; Junjiang Shu; Lei Liu; Jin Wang; Lijin Lin (Physiology and Molecular Biology of Plants, 2022)

Does the institutional environment influence corporate social responsibility? Consideration of green investment of enterprises—evidence from China - Shu-Rong Han; Pei Li; Jian-Jun Xiang; Xiang-Hua Luo; Chun-Yan Chen (Environmental Science and Pollution Research, 2022)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Activation of autophagy reverses gemcitabine-induced immune inhibition of RAW264.7 macrophages by promoting TNF-α, IL-6 and MHC-II expression - Shanshan Jiang; Rong Wang; Lu Han; Kudelaidi Kuerban; Li Ye; Shu Pan; Shengnan Li; Yongfang Yuan (Immunologic Research, 2021)
This research aims to investigate the effect of gemcitabine (GEM) on various activities and functions of macrophages. Phagocytosis, cell autophagy and reactive oxygen species (ROS) were analysed by laser scanning confocal microscope. The cell cycle status and major histocompatibility complex II (MHC-II) expression were examined by flow cytometry. Inflammatory cytokine secretion such as tumour necrosis factor α (TNF-α) and interleukin 6 (IL-6) was detected by Elisa assay. The expression of proteins was analysed by western blot method. The results revealed that GEM-induced immune inhibition of M1-type RAW264.7 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS). We also found that GEM inhibited autophagy, as evidenced by the reduced formation of autophagosome-like vacuoles and autophagosomes. Further study showed that incubation of activated macrophages with the autophagy inhibitor 3-MA induced immune suppression. In contrast, treatment with the autophagy inducer trehalose (Tre) restored phagocytosis, TNF-α and IL-6 secretion, and MHC-II expression in GEM-induced immune-inhibited macrophages. GEM reduced immune effect of M1-type RAW264.7 macrophages via inhibiting TNF-α, IL-6 and MHC-II expression. Furthermore, activation of autophagy by Tre reversed GEM-induced immune inhibition of RAW264.7 macrophages.

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

Analysis of slight precipitation in China during the past decades and its relationship with advanced very high radiometric resolution normalized difference vegetation index - Xinyue Li; Yves Balkanski; Zhengfang Wu; Thomas Gasser; Philippe Ciais; Feng Zhou; Laurent Li; Shu Tao; Shushi Peng; Shilong Piao; Rong Wang; Tao Wang; et al. (International Journal of Climatology, 2018)
Precipitation is one of the most important factors determining the occurrence of extreme hydro‐meteorological events and water resource availability. Precipitation in different grades has diverse ecological effects, and slight precipitation (SP, defined as 0.1–1.0 mm/day) is the minimal level among them. In this study, we investigated SP trends from 1961 to 2013, as well as the relationship between SP and advanced very high radiometric resolution (AVHRR) normalized difference vegetation index (NDVI) in China during growing season from 1981 to 2006. The distributions and trends of SP were analysed by calculating the daily precipitation data. The average annual slight precipitation amount (SPA) and the number of slight precipitation days (SPD), derived from 839 monitoring stations in China, show a decreasing trend over the last five decades, which is in agreement with total precipitation (TP) but in different rates. When the trend was analysed seasonally, SP in most stations decreases significantly in September–October–November (SON) and June–July–August (JJA), and the largest decrease is found in SON. About 49.5 and 68.7% of monitoring stations show a decreasing trend in SON, in both SPA and SPD, whereas the trend is less popular in March–April–May (MAM, SPA: 19.7%, SPD: 41.4%) and December–January–February (JJF, SPA: 25.6%, SPD: 43.1%). Moreover, our analysis indicates that the decrease of SP is mainly due to the decrease of SPD as the median amount of daily SP was unchanged over the past five decades (close to 0.3 mm/day). Based on 26‐year (1981–2006) semi‐monthly AVHRR NDVI data and the records of SP data, the relationship between AVHRR NDVI and SP was also investigated. In regions with lower (

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Polyol monoterpenes isolated from Chenopodium ambrosioides - Shu-Qun Hou; Yan-Hong Li; Xiang-Zhong Huang; Rong Li; Huai Lu; Kai Tian; Rong-Sheng Ruan; Yu-Kui Li (Natural Product Research, 2017)

Global forest carbon uptake due to nitrogen and phosphorus deposition from 1850 to 2100 - Rong Wang; Daniel Goll; Yves Balkanski; Didier Hauglustaine; Olivier Boucher; Philippe Ciais; Ivan Janssens; Josep Penuelas; Bertrand Guenet; Jordi Sardans; Laurent Bopp; Nicolas Vuichard; et al. (Global Change Biology, 2017)
Spatial patterns and temporal trends of nitrogen (N) and phosphorus (P) deposition are important for quantifying their impact on forest carbon (C) uptake. In a first step, we modeled historical and future change in the global distributions of the atmospheric deposition of N and P from the dry and wet deposition of aerosols and gases containing N and P. Future projections were compared between two scenarios with contrasting aerosol emissions. Modeled fields of N and P deposition and P concentration were evaluated using globally distributed in situ measurements. N deposition peaked around 1990 in European forests and around 2010 in East Asian forests, and both increased sevenfold relative to 1850. P deposition peaked around 2010 in South Asian forests and increased 3.5‐fold relative to 1850. In a second step, we estimated the change in C storage in forests due to the fertilization by deposited N and P (∆C ν dep ), based on the retention of deposited nutrients, their allocation within plants, and C:N and C:P stoichiometry. ∆C ν dep for 1997–2013 was estimated to be 0.27 ± 0.13 Pg C year −1 from N and 0.054 ± 0.10 Pg C year −1 from P, contributing 9% and 2% of the terrestrial C sink, respectively. Sensitivity tests show that uncertainty of ∆C ν dep was larger from P than from N, mainly due to uncertainty in the fraction of deposited P that is fixed by soil. ∆ C P dep was exceeded by ∆ C N dep over 1960–2007 in a large area of East Asian and West European forests due to a faster growth in N deposition than P. Our results suggest a significant contribution of anthropogenic P deposition to C storage, and additional sources of N are needed to support C storage by P in some Asian tropical forests where the deposition rate increased even faster for P than for N.

Chronological constraints on the tectonic evolution of the Chinese Tianshan Orogen through detrital zircons from modern and palaeo-river sands - Rong Ren; Shu-Wei Guan; Bao-Fu Han; Li Su (International Geology Review, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Stability analysis of slope in strain-softening soils using local arc-length solution scheme - Xiang-rong Wang; Qi-guo Rong; Shu-li Sun; Hui Wang (Journal of Mountain Science, 2017)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)

The effects of grafting on glycolysis and the tricarboxylic acid cycle in Ca(NO3)2-stressed cucumber seedlings with pumpkin as rootstock - Lin Li; Wen-wen Xing; Qiao-sai Shao; Sheng Shu; Jin Sun; Shi-rong Guo (Acta Physiologiae Plantarum, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Effects of Plant Stress Signal Molecules on the Production of Wilforgine in an Endophytic Actinomycete Isolated from Tripterygium wilfordii Hook.f. - Guo-peng Miao; Chuan-shu Zhu; Jun-tao Feng; Li-rong Han; Xing Zhang (Current Microbiology, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Over-expression of SlWRKY39 leads to enhanced resistance to multiple stress factors in tomato - Xiao-chun Sun; Yong-feng Gao; Hui-rong Li; Shu-zhang Yang; Yong-sheng Liu (Journal of Plant Biology, 2015)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Association between melatonin receptor 1A (MTNR1A) gene single-nucleotide polymorphisms and the velvet antler yield of Sika deer - Fei-Fei Yang; Li-Jun Huo; Li-Guo Yang; Hasan Riaz; Li-Rong Xiong; Jian-Guo Chen; Shu-Jun Zhang; Jia-Jun Xiong (Molecular Biology Reports, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Molecular and pathogenic characterization of new Xanthomonas oryzae pv. oryzae strains from the coastline region of Fangchenggang city in China - Shu-Qing Yang; Shu-Yan Liu; Shuai Zhao; Yan-Hua Yu; Rong-Bai Li; Cheng-Jie Duan; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Differential Effects of Legume Species on the Recovery of Soil Microbial Communities, and Carbon and Nitrogen Contents, in Abandoned Fields of the Loess Plateau, China - Jin Hua Li; Shu Mei Jiao; Rong Qing Gao; Richard D. Bardgett (Environmental Management, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses - Si-Ying Wu; Huang-Yuan Li; Shu-Juan Yang; Wei Zhu; Xiao-Rong Wang (International Archives of Occupational and Environmental Health, 2012)

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Comparative Analysis of Endogenous Hormones in Leaves and Roots of Two Contrasting Malus Species in Response to Hypoxia Stress - Tuanhui Bai; Rong Yin; Cuiying Li; Fengwang Ma; Zhiyong Yue; Huairui Shu (Journal of Plant Growth Regulation, 2011)

Effects of elevated CO2 levels on root morphological traits and Cd uptakes of two Lolium species under Cd stress - Yan Jia; Shi-rong Tang; Xue-hai Ju; Li-na Shu; Shu-xing Tu; Ren-wei Feng; Lorenzino Giusti (Journal of Zhejiang University-SCIENCE B, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Validation of eight names of Chinese taxa in Ranunculaceae, Rosaceae and Scrophulariaceae - Qi Lin; Miao Sun; Qian Sun; Shu-Qing Bei; Hong-Li Li; Zhi-Rong Yang (Kew Bulletin, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Cytogenetic Study of a Trigeneric (Triticale × Trileymus) Hybrid - Xing-Feng Li; Zhen-Qiao Song; Shu-Bing Liu; Ju-Rong Gao; Hong-Gang Wang (Euphytica, 2006)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)

Abnormal pollen development of bread wheat-Leymus mollis partial amphiploid - Xing-Feng Li; Shu-Bing Liu; Ju-Rong Gao; Wen-Hui Lu; Hong-Gang Wang (Euphytica, 2005)